Chief physicians' attitudes towards early warning score systems in Switzerland: Results of a cross‐sectional survey. Issue 2 (8th November 2017) - Richard, Aline; Frank, Olga; Schwappach, David
Abstract: Rationale, aims and objectives: Early warning score systems (EWS‐S) have been shown to be valuable tools to recognize otherwise unnoticed clinical deterioration (CDET) of patients. They have been associated with fewer unplanned transfers to the intensive care unit (UTICU) and lower in‐hospital mortality. Little is known about their current usage in Switzerland and about the attitudes towards such tools among chief physicians. We aimed to assess the use of EWS‐S in Switzerland and the attitudes of chief physicians towards EWS‐S depending on previously experienced CDET followed by UTICU, reanimation, or death. Methods: Chief physicians of medical and surgical departments from all acute care hospitals in Switzerland were asked to participate within a project that aims to develop recommendations for the use of EWS‐S in Switzerland (n = 118). The explorative study assessed perceived CDET, which led to UTICU, reanimation, or death of a patient, the knowledge and usage about different EWS‐S and attitudes towards EWS‐S in a written questionnaire. Means and percentages were used, and differences were assessed with independent t tests, chi‐square, or Fisher exact test, as appropriate. Results: Adverse events based on CDET were reported frequently, and awareness among chief physicians was high. Less than half of the chief physicians knew tools that systematically assess CDET with one‐fifth of responders reporting using tools at their department. Previous experiences of UTICU, reanimation, or death after due to CDET were associated with more positive attitudes towards EWS‐S. Conclusions: Adverse events based on CDET of patients are frequent and the awareness of this problem is high among chief physicians. Positive attitudes were more common with previous experiences of adverse events due to CDET. Our results strengthen the argumentation that the recommendation and future implementation of EWS‐S in Switzerland would be meaningful.